Regional sanctions and the struggle for democracy: Introduction to the special issue. Issue 4 (September 2021) - Hellquist, Elin; Palestini, Stefano
Regional organisations (ROs) around the world increasingly use sanctions against member states in situations of democratic crisis. This special issue unpacks the trend of RO sanctions in regions that are both democracy-dense (Europe and the Americas) and autocracy-dense (Africa, Southeast Asia, and the Middle East). We argue that regional sanctions cannot be taken at face value as instruments of democracy promotion. Instead, the politics of regional sanctions unveil controversies over the substance and limits of democracy, as well as over practical processes of regional interference in a sphere that is at the core of 'domestic affairs'. In this introductory article, we situate the special issue at the crossroads of debates within comparative regionalism, sanctions, and democracy/autocracy promotion, and discuss how the membership premise crucially distinguishes RO measures from foreign policy and United Nations (UN) sanctions.